Fiber Strength After Grain Growth in Nextel™ 610 Alumina Fiber. Issue 6 (23rd March 2015) - Hay, Randall S.; Fair, Geoff E.; Tidball, Travis; Chan, H.
<x xml:space="preserve">Abstract</x> Nextel™ 610 alumina fiber tows were heat‐treated at 1100°C–1500°C for 1 to 100 h in air. Tensile strengths and Weibull moduli were measured for 30 filaments after each heat‐treatment. 3‐D grain size and orientation distributions were described using oblate ellipsoids. The number of grains in a 1 inch gauge length and grains with the largest major and minor ellipsoid‐axes were determined from these distributions. The grain with the largest KEFF for mixed‐mode fracture was also determined, using the maximum energy release rate criteria from grain‐size and orientation distributions. Grain‐size dependence of tensile strength and Weibull modulus was evaluated. Strength had no obvious dependence on grain size for fibers with average major‐axes smaller than 0.25 μm. For fibers with larger grains, grain‐size dependence may involve flaws originating from clumps of grains, rather than a single grain. Possible relationships between strength and grain‐size and other causes of strength degradation after heat‐treatment are discussed.